BuZangTongLuo decoction improved hindlimb ischemia by activating angiogenesis and regulating gut microbiota in diabetic mice. (10th February 2020) - Zheng, Junping; Chen, Man; Ye, Cheng; Sun, Xiongjie; Jiang, Nan; Zou, Xiaojuan; Yang, Huabing; Liu, Hongtao
Abstract: Ethnopharmacological relevance: Seven traditional medicinal plants (including Astragalus membranaceus, Dioscorea hemsleyi, Salvia miltiorrhiza, Scrophularia ningpoensis, Ophiopogon japonicus, Panax ginseng and Fritillariae cirrhosae ) and one insect leech ( Whitmania pigra Whitman ) were combined into BuZangTongLuo formula (BZTLF) under the guidance of traditional Chinese medicine. BZTLF is potentially effective against diabetic vascular complications. Aim of the study: Previous studies failed to clarify the molecular mechanism through which BZTLF suppressed diabetic ischemia. In this study, we aimed to explore whether BZTLF treatment could prevent the occurrence of type 2 diabetic (T2D) hindlimb ischemia in mice. Further, we investigated the regulatory effect of BZTLF on angiogenesis-related VEGF signaling pathway and gut microbiota dysfunction in diabetic ischemia mice. Materials and methods: C57BL/6J mice fed with high-fat diet (HFD) received STZ injection and femoral artery ligation to build T2D diabetic hindlimb ischemia model. Mice were gavaged with BZTLF (5 g [raw materials]/kg/d) or with metformin plus atorvastatin for three weeks. Laser doppler imaging system was utilized for the visualization of blood flow. Histochemistry analysis was performed for microvascular vessel staining. Western blot was applied to detect the protein changes of signaling molecules responsible for VEGF pathway. Finally, 16S rDNA gene sequencing was conducted for analysis of gut microbiota structure. Results: BZTLF treatment remarkably restored blood flow and capillary density of diabetic hindlimb ischemia. And the protein changes of VEGF signaling molecules were reversed in BZTLF-treated diabetic ischemia mice, including the decreased VEGF and HIF-1α, and the increased NO, eNOS and p-ERK1/2. The gut microbiota analysis suggests that BZTLF treatment increased the abundances of several beneficial bacteria ( Akkermansia, Bifidobacterium and Bacteroides ), while decreased the populations of some harmful bacteria( Blautia, Weissella, Escherichia Shigella and Kurthia ). By using Spearman's correlation analysis, these changed gut flora were positively/negatively correlated with VEGF signaling pathway or glycometabolic parameters. Conclusion: BZTLF displayed beneficial effects on diabetic hindlimb ischemia by reshaping the gut microbiota structure and stunning the VEGF/HIF-1α pathway. Graphical abstract: Image 1